Pengaruh Struktural Kepemilikan Saham dan Profitabilitas Terhadap Nilai Perusahaan - Ferdy Putra (Akuntansi & Ekonomika, 2020)
This study aims to determine the effect of ownership structure (institutional ownership and managerial ownership) and profitability on firm value at Manufacturing companies in Indonesia Stock Exchange. Research conducted on a manufacturing company on the Indonesia Stock Exchange in the 2016-2018 observations period. By using purposive sampling method, obtained a sample of 48 companies. Data were analyzed using multiple regression. Based on the results of this study concluded that managerial ownership significant effect on firm value. Institutional ownership significant effect on firm value and profitability significant effect on firm value.